Uncovering the Determinants of Auditor Switching - Adyatma Daniswara, Vincentius; Amirya, Mirna (TEMA, 2025)
Research related to auditor switching determinants is important to provide stakeholders with an understanding of the factors that influence auditor switching so that it can be used as a basis for their decision-making. This study aims to examine the effects of going concern audit opinions, audit delay, auditor reputation, and financial distress on auditor switching, which is proxied using dummy variables based on agency theory, in transportation and logistics companies listed on the Indonesia Stock Exchange. Using purposive technique, 100 samples from 25 companies were collected. Those secondary data were obtained from financial statements for the 2020–2023 period available on the Indonesia Stock Exchange (IDX) or the sample companies’ websites and were analyzed using logistic regression in SPSS version 25. The findings show that auditor reputation has a negative effect on auditor switching, while going concern audit opinions, audit delay, and financial distress have no effect on auditor switching. This study implies that auditor reputation can guide investor and creditor decisions, and management should retain reputable auditors to uphold audit quality and trust, while considering other factors influencing auditor switching. This study enhances prior research by using the Altman Z-score for financial distress and a three-tier classification of auditor reputation that provides more comprehensive findings for stakeholders in evaluating auditor switching decisions.